2015
DOI: 10.1149/2.0251602jss
|View full text |Cite
|
Sign up to set email alerts
|

Review—Ionizing Radiation Damage Effects on GaN Devices

Abstract: Gallium Nitride based high electron mobility transistors (HEMTs) are attractive for use in high power and high frequency applications, with higher breakdown voltages and two dimensional electron gas (2DEG) density compared to their GaAs counterparts. Specific applications for nitride HEMTs include air, land and satellite based communications and phased array radar. Highly efficient GaNbased blue light emitting diodes (LEDs) employ AlGaN and InGaN alloys with different compositions integrated into heterojunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
130
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(148 citation statements)
references
References 191 publications
4
130
0
3
Order By: Relevance
“…However, the rate of recovery observed in this work is rather surprising since the recovery time of several weeks at room temperature is usually reported in the literature. 39 Self-annealing of irradiation induced defects at room temperature is reported over a month period in the case of the InGaAs/GaAs quantum well by Dhaka et al 40 Similarly, a self-recovery of neutron irradiated AlGaN/GaN high electron mobility transistor (HEMT) devices is reported by Kim et al 41 where the electrical response of the device completely recovered within 3 weeks of irradiation. The only difference is that our devices recover within a day which might be governed by the extent of damage caused by a different type of irradiation in our experiments.…”
Section: à3mentioning
confidence: 96%
“…However, the rate of recovery observed in this work is rather surprising since the recovery time of several weeks at room temperature is usually reported in the literature. 39 Self-annealing of irradiation induced defects at room temperature is reported over a month period in the case of the InGaAs/GaAs quantum well by Dhaka et al 40 Similarly, a self-recovery of neutron irradiated AlGaN/GaN high electron mobility transistor (HEMT) devices is reported by Kim et al 41 where the electrical response of the device completely recovered within 3 weeks of irradiation. The only difference is that our devices recover within a day which might be governed by the extent of damage caused by a different type of irradiation in our experiments.…”
Section: à3mentioning
confidence: 96%
“…However some recent reports do exist for the same materials as used for the Cree XP-E2 LEDs. Blue LEDs made of InGaN are reported to decrease its luminance by about 18% and 47% for 340 keV proton doses of respectively 1x10 12 and 5 x 10 12 proton/cm 2 [4]. The InGaN is the same technology used for the green Cree XP-E2 LED that during the CHARM test shows a decrease of about 30% for a dose of 870 Gy and 2.3 x 10 12 HEH/cm 2 .…”
Section: Radiation Testsmentioning
confidence: 98%
“…The technology is particularly appealing for microwave power amplifiers and direct current (DC)/DC converters in space‐based applications due to the high tolerance to the space radiation environment. It has previously been shown that the DC I–V characteristics exhibit high‐tolerance displacement damage induced by proton irradiation and devices exhibit reduced leakage current and increased breakdown voltage but at the expense of substantially increased dynamic ON resistance . However, there has not been a thorough spectroscopic evaluation of such device structures to identify the nature of the traps induced by displacement damage.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the DC I-V characteristics exhibit high-tolerance displacement damage induced by proton irradiation and devices exhibit reduced leakage current and increased breakdown voltage but at the expense of substantially increased dynamic ON resistance. [1][2][3][4][5] However, there has not been a thorough spectroscopic evaluation of such device structures to identify the nature of the traps induced by displacement damage.…”
Section: Introductionmentioning
confidence: 99%